Mapping the Research Landscape of Chatbots, Conversational Agents, and Virtual Assistants in Business, Management, and Accounting: A Bibliometric Review - Manigandan L; Sivakumar Alur (Qubahan Academic Journal)
This bibliometric review aims to map the research landscape of chatbots, conversational agents, and virtual assistants in the business, management, and accounting of the subject area. The review begins by examining the growth of research in this area over time, revealing an increasing interest in the application of chatbots, conversational agents, and virtual assistants in business, management, and accounting contexts. This study aims to contribute to the field of chatbot research by conducting a bibliometric analysis of chatbot, conversational agent and virtual assistant papers available in the Scopus databases. A comprehensive analysis of 378 articles was performed utilizing the Bibliometrix software package. The keywords "Chatbot", "conversational agent" and “virtual assistant” emerged as the most frequently employed terms in the majority of publications. It explores the various domains within which these technologies have been studied, including customer service, marketing, human resources, and financial management.